How to secure your supply chain. Issue 3 (March 2019) - Duncan, Rory
Abstract : Security investments are finally starting to bear fruit. Research shows outsourced incident response engagements against financial institutions – the most targeted sector for cyber attacks in 2016 – have dropped off significantly. Companies are seemingly waking up to the realisation that their core business processes need serious bolstering to keep the bad guys out.